The Effect of Blood Adding Tablet Consumption on Hb Levels of Pregnant Women at the Silau Laut Health Center, Silau District, Asahan Regency in 2021 - Suhartini (Science Midwifery, 2022)
Factors that cause birth weight babies include lack of Hb levels in pregnant women. Lack of hemoglobin (Hb) levels of less than 11 g/dl. Anemia in pregnant women increases the risk of getting a Low Newborn Baby (LBW), the risk of bleeding before and during delivery, can even cause the death of the mother and baby if the pregnant woman suffers from severe anemia. The purpose of this study was to determine the effect of blood-supplementing tablet consumption on pregnant women's Hb levels at the Silau Laut Health Center, Silau District, Asahan Regency in 2021. This type of research is cross sectional with analytic character. The population in this study were all pregnant women living in the working area of ​​the Sialu Laut Health Center as many as 165 people, a sample of 25 people was taken, using acidental sampling. The data collected in the study is primary data, namely data obtained directly from respondents. The data analysis used is univariate analysis and bivariate analysis. The results of the pree tabulation of the consumption of blood-added tablets on the Hb level of pregnant women, namely the majority experienced anemia as many as 16 (64%) respondents with a Mean value of 0.36, Standard Deviation value of 0.490, Standard Error value of 0.098. The results of the tabulation of post-consumption of blood-added tablets on the Hb level of pregnant women were the majority not anemic as many as 22 (88%) respondents with a Mean value of 0.88, a Standard Deviation value of 0.332, a Standard Error value of 0.066. The average consumption of blood enhancing tablets from 25 respondents with a Mean - 0.520, Standard error 0.117, and Standard Deviation 0.586. statistical test results obtained -value = 0.000 which means that there is an effect of consuming blood-enhancing tablets on pregnant women's HB levels All health workers at the Silau Laut Health Center are expected to be more active in implementing posyandu for pregnant women and providing health education related to healthy pregnancy to pregnant women and how to safely consume blood boosting tablets.